A systematic review and meta-analysis of perioperative oral decontamination in patients undergoing major elective surgery. Issue 1 (December 2016) - Spreadborough, Philip; Lort, Sarah; Pasquali, Sandro; Popplewell, Matthew; Owen, Andrew; Kreis, Irene; Tucker, Olga; Vohra, Ravinder
Abstract Background Oral antiseptics reduce nosocomial infections and ventilator-associated pneumonia in critically ill medical and surgical patients intubated for prolonged periods. However, the role of oral antiseptics given before and after planned surgery is not clear. The aim of this systematic review and meta-analysis is to determine the effect of oral antiseptics (chlorhexidine or povidone–iodine) when administered before and after major elective surgery. Methods Searches were conducted of the MEDLINE, EMBASE and Cochrane databases. The analysis was performed using the random-effects method and the risk ratio (RR) with 95 % confidence interval (CI). Results Of 1114 unique identified articles, perioperative chlorhexidine was administered to patients undergoing elective surgery in four studies. This identified 2265 patients undergoing elective cardiac surgery, of whom 1093 (48.3 %) received perioperative chlorhexidine. Postoperative pneumonia and nosocomial infections were observed in 5.3 and 20.2 % who received chlorhexidine compared to 10.4 and 31.3 % who received a control preparation, respectively. Oral perioperative chlorhexidine significantly reduced the risk of postoperative pneumonia (RR = 0.52; 95 % CI 0.39–0.71;p  < 0.01) and overall nosocomial infections (RR = 0.65; 95 % CI 0.52–0.81;p  < 0.01), with no effect on in-hospital mortality (RR = 1.01; 95 % CI 0.49–2.09;p  = 0.98). Conclusions Perioperative oral chlorhexidine significantly decreases the incidence of nosocomial infection and postoperative pneumonia in patients undergoing elective cardiac surgery. There are no randomised controlled studies of this simple and cheap intervention in patients undergoing elective non-cardiac surgery. Trial Registration This systematic review was registered with the International prospective register of systematic reviews (PROSPERO). The registration number is CRD42015016063.